Comparison of Functionality of Type A And B Guide Rails of Steel Road Safety Barriers - Daniel Bronislaw Nycz (The Baltic Journal of Road and Bridge Engineering)
The subject of the work is types A and B guide rails of steel road barriers. An experimental three-point bend test on a segment of a B-type guide rail was conducted for experimental validation of the numerical modelling of the guide rail. Numerical modelling of bend tests on A and B guide rail segments was performed. It was shown that the load-bearing capacity and energy absorbed during bending for guide rail A are more than for guide rail B, respectively. Numerical TB32 crash tests (a 1500 kg vehicle, 110 km/h impact speed, 20° impact angle) were carried out in the LS-Dyna system. The Dodge Neon vehicle model was downloaded from the National Crash Analysis Centre in the United States. A 60 m long barrier section is composed of A or B guide rail segments, SIGMA-100 posts, trapezoidal supporting elements and rectangular pads. Each segment has a total length of 4.30 m and an efficient length of 4.00 m. SIGMA-100 posts are 1.90 m long and spaced by 2.00 m. The whole barrier is assembled with M16 screws with a spherical head and a nose, strength class 4.6. The simulated crash tests showed slight differences in the functionality of guide rails A and B regarding the TB32 crash test.